Ethnicity, location, age, and fluoridation factors in baby bottle tooth decay and caries prevalence of Head Start children. - Barnes, G P (1992)
Baby bottle tooth decay (BBTD) is a term applied to a specific form of rampant decay associated with inappropriate bottle or breast feeding of infants and young children. Although the prevalence of BBTD has been studied in individual ethnic groups, comparison studies are rare. Head Start children have frequently served as study subjects for assessing the prevalence of BBTD. The purpose of this study was to compare BBTD and caries prevalence among Head Start children who are members of four ethnic groups in five southwestern States. Age, residence, and fluoridation status were also compared for the total sample and ethnic categories. The sampling process was a stratified random site selection; it was used to obtain data on 1,230 children. This number constituted 3 percent of the children enrolled in Head Start in Public Health Service Region VI (Arkansas, Louisiana, New Mexico, Oklahoma, and Texas) where the study was conducted. The criterion for determining the presence of BBTD was based on the number of carious deciduous maxillary incisors observed. The severity of the condition was reported as two of four and three of four of the target teeth affected. Thus, two levels of severity are reported. BBTD was prevalent in approximately 24 percent and 15 percent of the total sample, depending on the severity criterion used. Native American children had a significantly higher (P less than 0.05) prevalence than Hispanic, white, and black subjects. Rural children had significantly higher (P less than 0.05) prevalence of BBTD than nonrural children for all ethnic groups except whites.(ABSTRACT TRUNCATED AT 250 WORDS)